'What would a trauma‐informed mental health service look like?' Perspectives of people who access services. (21st November 2020) - Isobel, Sophie; Wilson, Allyson; Gill, Katherine; Howe, Deborah
Abstract: Trauma‐informed care is an approach to the delivery of mental health care based on an awareness of the high prevalence of trauma in the lives of people accessing mental health services, the effects of trauma experiences and the potential for trauma or re‐traumatization to occur in the context of care. Across Australia, inquiries and reports have increasingly indicated an urgent need for mental health services to become trauma‐informed. However, how Australian mental health services should deliver trauma‐informed care is not well documented. Efforts towards trauma‐informed care in any setting require engagement with those who receive care. This qualitative study used an experience‐based co‐design methodology to explore the perspectives of consumers of mental health services in Australia and their family members, in relation to the question 'what would a trauma‐informed mental health service look like?' Focus groups were held with consumers ( n  = 10) and carers ( n  = 10). Thematic analysis of transcripts identified that consumers and carers consider that trauma‐informed care requires increased awareness of trauma amongst mental health staff, opportunities to collaborate in care, active efforts by services to build trust and create safety, the provision of a diversity of models and consistency and continuation of care. The findings provide important new information about the experiences of Australian service users and have implications for the implementation of trauma‐informed care across settings.